Genome-wide definitive haplotypes determined using a collection of complete hydatidiform moles - Kukita, Yoji; Miyatake, Katsuyuki; Stokowski, Renee; Hinds, David; Higasa, Koichiro; Wake, Norio; Hirakawa, Toshio; Kato, Hidenori; Matsuda, Takao; Pant, Krishna; Cox, David; Tahira, Tomoko; et al.

(untitled) (Genome Research, 2005)
We present genome-wide definitive haplotypes, determined using a collection of 74 Japanese complete hydatidiform moles, each carrying a genome derived from a single sperm. The haplotypes incorporate 281,439 common SNPs, genotyped with a high throughput array-based oligonucleotide hybridization technique. Comparison of haplotypes inferred from pseudoindividuals (constructed from randomized mole pairs) with those of moles showed some switch errors in resolution of phases by the computational inference method. The effects of these errors on local haplotype structure and selection of tag SNPs are discussed. We also show that definitive haplotypes of moles may be useful for elucidation of long-range haplotype structure, and should be more effective for detecting extended haplotype homozygosity indicative of positive selection.